resolva as expressões abaixo:
a) (3/2 - 2/5) + (5/4 - 2/3) =
b) (7/8 - 5/6) + (8/9 -7/9) =
c) [(3/5)² : 27/25] : 1/6 =
d) [12/169 . (13/2)² : 3/5 + 1 ]² - 11/4 =
Soluções para a tarefa
Respondido por
3
Resposta:
Vê o anexo, só n consegui responder a d) inteira
Anexos:
![](https://pt-static.z-dn.net/files/d1f/6741e09175172fbab9b6b151c79703bc.png)
Perguntas interessantes
Geografia,
8 meses atrás
Geografia,
8 meses atrás
Biologia,
8 meses atrás
Português,
9 meses atrás
Matemática,
9 meses atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás